The international politics of tolerance in the Persian Gulf. Issue 4 (2nd October 2018) - Fahy, John
ABSTRACT: Since the early 2000s, wide-ranging initiatives geared towards the promotion of tolerance, moderation and interfaith dialogue have proliferated throughout the Persian Gulf, culminating most recently in the establishment of the world's first Ministry of Tolerance in the UAE. For more than a decade, Qatar has hosted annual interfaith conferences on themes such as 'Steps Towards Tolerance'. Oman and Bahrain have been prominent advocates, pursuing their respective tolerance agendas through academic publications, travelling delegations, exhibitions and international conferences. Even Saudi Arabia, notorious for its intolerance at home, has been a prominent advocate on the world stage. Talk of tolerance, it seems, is everywhere, but what is behind this regional trend? This article situates the emergent political discourse of tolerance in the broader post-9/11 geopolitical context, wherein the ideal of tolerance has been embraced by both the West and the Muslim world as an antidote to the global problem of terrorism. I suggest that Gulf tolerance initiatives are best understood in terms of a broader politics of representation that coheres around the promotion of 'moderate Islam', and that in the context of what has been described as the Western 'civilisational discourse' of tolerance, Muslim-majority countries are responding with a civilisational discourse of their own.